TikTokisation and YouTubefication of learning contents and students’ learning outcomes in Spoken English - Kehinde Ogunyemi; Deborah Mohammed (Erudita: Journal of English Language Teaching, 2026)
This study examines the potential of social media platforms, specifically TikTok and YouTube, in enhancing the spoken English proficiency of Nigerian students. Using a pretest-posttest quasi-experimental design, the study compared three groups: one exposed to TikTok (TikTokisation), one exposed to YouTube (YouTubefication), and a control group taught with conventional methods. The research assessed the effectiveness of these platforms in improving spoken English skills and explored students’ attitudes toward using them as learning tools. The results revealed significant improvements in spoken English achievement for both the TikTok and YouTube groups compared to the control group, with mean scores of 41.23 and 42.56, respectively, surpassing the conventional group’s score of 35.43. However, no significant differences were found in the students’ attitudes toward learning English between the experimental and control groups. These findings suggest that while TikTok and YouTube are effective tools for enhancing language proficiency, they do not significantly alter students' overall attitudes toward learning. The study highlights the potential of integrating digital platforms with traditional learning methods to improve spoken English proficiency and recommends further research into strategies that can foster more positive attitudes toward language learning.